TINJAUAN KRIMINOLOGIS TENTANG TINDAK PIDANA PENYALAHGUNAAN IZIN TINGGAL KEIMIGRASIAAN - Apriani Putri Ananda; Baharuddin Badaru; Ernawati Djabur (Qawanin Jurnal Ilmu Hukum, 2021)
ABSTRACT Background The writing of this journal is motivated by the problems, the factors that cause the misuse of residence permits by foreign citizens and to find out law enforcement against the abuse of residence permits by residents of Makassar. Immigration office of the ministry of law andhuman rights in overcoming abuses of residence permits by foreign nationals. This search uses desvriptive qualilative research methods anduses the type of empirical research including secondary data and primary data using observation, documentation and field interviews. This research was conducted in Makassar, tha ministry of law and human right of the South Sulawesi Regional office. The results of this study indicate that the Makassar Ministry of law and human rights, South Sulawesi Regional office in dealing with abuse of immigration residence permits has acted un accordance with law concerning immigration. The abuse actor for foreigners can be due to the factor of the toreigner making aresidence permit without existing procedures. The discussion of the results of this study shows that the law enforcement of criminal acts of abuse of residence permits immigracy is carried out by the immigration administrative action of the class I immigration office of Makassar city. Research recommendations in the implementation of immigration officersmust increase awareness of the presence and activities of foreigners in Makassar and pro justice in law enforcement actions to ensure a deterrent effect on perpetrators of residence permit abuse and foreigners who commit violations so as not to commit the same immigration crime, and it is hoped that the people of Makassar To work closely with immigration officials to make complaints about the presence or activities of foreigners who are nearby. ABSTRAK Latar belakang Penulisan jurnal ini dilatar belakangi oleh permasalahan, faktor-faktor penyebab penyalahgunaan izin tinggal oleh warga negara asing dan untuk mengetahui penegakan hukum terhadap penyalahgunaan izin tinggal oleh warga Makassar. kanwil kemenkumham dalam mengatasi penyalahgunaan izin tinggal oleh warga Negara asing. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dan menggunakan jenis penelitian empiris dengan mengcakup data skunder dan data primer menggunakan observasi, dokumentasi dan wawancara dilapangan. Penelitian ini dilakukan di Makassar kementrian hukum dan asasi manusia kanwil sulsel. Hasil penelitian ini menunjukkan bahwa Makassar kemenkum ham kanwil sulsel dalam hal mengatasipenyalahgunaan izin tinggal keimigrasian telah bertindak sesuai dengan Undang-undang Faktor penyalahgunaan bagi orang asing dapat dikarenakan faktor orang asing tersebut yang melakukan izin tinggal tanpa prosedur yang ada. pembahasan dari hasil penelitian ini menunjukkan bahwa penegakan hukum tindak pidana penyalahgunaan izin tinggal keimigrasiaan dilakukan oleh tindakan administratifkeimigrasian kantor imigrasi kelas I kota Makassar. Rekomendasi penelitian dalam pelaksanaan petugas imigrasi harus meningkatkan pegawasan terhadap keberadaan dan kegiatan orang asing dimakassar dan pro keadilan dalam tindakan penegakan hukum untuk memastikan efek jera kepada pelaku penyalahgunaan izin tinggal dan orang asing yang malakukan pelanggaran agar tidak melakukan kejahatan imigrasi yang sama, dan diharapkan masyarakat Makassar untuk berkerja sama dengan petugas imigrasi untuk membuat keluhan tentang keberadaanatau kegiatan orang asing yang berada didekatnya.